Score equalisation in men`s and women`s olympic weightlifting (48-75 kg for women and 56-105 kg for men) - Haleczko, A. (Journal of Kinesiology and Exercise Sciences, 2014)
Purpose. Devising a new formula for equalizing scores in 75 kg and 105 kg weight classes. Basic procedures. The gathered material consisted of particular body mass data and Olympic weightlifting scores of 54 women in 48-75 kg weight classes, and of 63 men in 56-105 kg weight classes, obtained at international competitions in years 2008-2013; as well as of 145 women and 211 men in over - 75 kg and over-105 kg weight classes, from the same time period. A third factor was taken into consideration, namely the difference between the score and body mass. By means of power iteration, coefficients and their conversion to kilograms were selected. Equalized scores were arrived at by multiplying both elements. Main findings. The established criterion for efficient score equalization is the coefficient of variation, the lower it is, the better. The results obtained (for both men and women) did not exceed 1%, whereas after applying Sinclair coefficients, the measurements of variation proved much higher. Since the extent to which score equalization can be carried out is limited (113 and 138 kg), scores of contestants in both over - 75 kg and over-105 kg still need additional calculations. Conclusions. Bearing in mind how great an impact contestants` body mass has on scores, calculating scores should only be carried out for contestants of maximal body mass of 130-135 kg (women) and 150-155 kg (men).